Human interaction and cultural significance - Qamaruz Zaman, Faridah (Universiti Putra Malaysia Press, 2013)
Insects are pervasive in our lives. Sometimes we may wish them away e.g. when we are in the middle of a slumber and the buzzing of the mosquito is just so jarring plus the fear of the disease they may carry. The rising case of dengue remains one of the greatest challenges for the urbanites in Malaysia. A lovely summer in countries with four seasons can be spoiled by the hordes of insects flying into houses, and biting into our flesh. Still for all the discomfort that some insects cause, there are others who are intrinsically linked to our lifestyle and culture. Who has not savoured the deliciousness of the trickling and oozing they? Spread on a warm-buttred toast, is perfection in simplicity. Added to the untold benefits, it is truly a gift from God. Spare a thought for the laborious bee that produces not just honey, but also royal jelly, propolis, and beeswax.